Perbandingan Efektivitas Ruang Kantor Terbuka dan Tertutup terhadap Produktivitas Karyawan: Studi Kasus di Kantor X - Salsha Billa, Salfa; Nauri, Luan; Chaniago, Harmon (International Journal Administration, Business & Organization, 2025)
This study compares the effectiveness of open and closed office spaces in the Office Using direct observation and in-depth interviews, the study found that open spaces encourage collaboration and communication, although they can reduce privacy and increase noise. Meanwhile, closed spaces provide greater focus and privacy, ideal for individual tasks and confidential meetings. The findings suggest that a hybrid approach combining both layouts offers the most effective solution to accommodate a variety of work needs. Theoretically, this study highlights the importance of integrating psychological and task-based considerations in workspace design. Practically, it informs organizations about the value of flexible, activity-based office layouts that align with employees’ work styles. The novelty of this study lies in its context-specific analysis that combines observational data with user experiences, offering a more holistic perspective than previous research that often focuses on one type of layout. This highlights the need for adaptable office design to support employee well-being and productivity.